Development of a fungal biodeterioration index for lignocellulosic materials relevant to the food industry - Anaya Villalpanda, Matilde (2025)
Contaminated packaging materials may represent a potential risk in food processing environments, particularly when no prior treatment is applied. This study aimed to develop a quantitative method to classify the fungal biodeterioration of lignocellulosic materials commonly used in food-related applications. Six lignocellulosic supports were evaluated: coated cardboard, uncoated cardboard, corrugated cardboard, kraft paper, cupcake wrapper, and Waltman No. 5 filter paper (used as a positive control). The materials were inoculated with a spore suspension of Aspergillus ellipticus, a strain previously characterized by its high degradative activity. Fungal growth was assessed using a conventional agar-based method and a proposed technique involving mechanical resistance analysis with a texture analyzer. A new biodeterioration index (IBF) was introduced to quantify the reduction in physical resistance of each material due to fungal activity. The method allowed the classification of both the fungal strains degradative capacity and the susceptibility of each material. Additionally, an equivalence scale was established between fungal growth on filter paper and other materials. This quantitative approach enables rapid and reproducible evaluation of biodeterioration and may serve as a useful tool for quality control, food safety assurance, and the development of bio-based packaging materials in the food industry.